A comprehensive study on noise reduction methods of marine propellers and design procedures. (July 2019) - Ebrahimi, A.; Razaghian, A.H.; Seif, M.S.; Zahedi, F.; Nouri-Borujerdi, A.
Abstract: The noise generated by the propeller is one of the most important components of the vessels noise. Therefore, reducing this noise will significantly decrease the total noise of the vessel. Underwater noise of vessels has destructive effects on marine life. In addition, this noise affects the health and comfort of the crew and passengers of the ship. Moreover, high noise may cause warships to be detected easily. In this paper, first, common methods of noise reduction, including blade coating, modern propellers, propeller hub modification and ducted propellers are investigated. Then, relevant optimization methods are presented. Next, the effects of the geometric parameters like number of blades, propeller diameter, expanded area ratio, geometric pitch, rake and skew angles on the noise and the operational range of each parameter are studied. Finally, a new algorithm is suggested to optimally design a propeller considering hydrodynamics as well as acoustics concerns.